Staying Together - Wilson J. Judith (Cambridge english readers Level 4)
Ikuko goes to England to study, promising to return to Japan to get married. But in Birmingham, Ikuko not only discovers another way of life but also a great deal about herself. This is a powerful story about a love that is carried across three continents and even time itself